Strategi Pemasaran Digital dalam Meningkatkan Kesadaran Merek Biodef melalui Tik Tok Live Shopping - Variansyah, Alif Azriel; Sondari, Mery Citra (LPPM Universitas dr. Soebandi, 2023)
The objective of this study is to assess the influence of digital marketingstrategies through Tik Tok Live Shopping on increasing brand awareness for Biodef products. The concept of Brand Awareness is crucial in marketing, and this study connects variables such as Customer Trust, Influencers Credibility, and Customer Engagement with Brand Awareness. The research employs a quantitative method with Descriptive Analysis and Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the data. The results indicate that Customer Engagement has a positive and significant effect on Brand Awareness, emphasizing the importance of active customer interaction with Tik Tok Live Shopping content. Customer Trust also positively influences Customer Engagement, demonstrating that trust forms a strong foundation for more active participation. Influencers Credibility also has a positive and significant impact on Brand Awareness, highlighting the crucial role of influencer credibility in Brand Awareness. These findings provide insights into how digital marketing strategies, considering these factors, can enhance brand awareness for Biodef products through Tik Tok Live Shopping